Influence of the Weight of Mini Corm Fragments on the Rejection Power of Plantain (Musa sapientum L.) Ex-Situ at Gbadolite in the Democratic Republic of Congo - Médard, Molongo Mokondande; Cornélie, Nzibe Mindende; Jacques, Toteanago Mazingi; Bertin, Libwa Momi; Junior, Ambwa Lokula (Budapest International Research and Critics University, 2023)
This study tested the influence of bulb fragments on the rejection potential of plantain ex-situ. The experimental set-up chosen was that of randomized complete blocks comprising 4 blocks and 4 treatments according to the weights of the minisets. Treatments were assigned to line plots under ex-situ conditions. They were made up of the following fragments: T0 (20g fragment), T1 (5g fragment), T2 (10g fragment), and T3 (15g fragment) at a rate of 150 minisets per treatment installed on a propagator in a greenhouse. For each bulb, 4, 17, 18 and 21 rejections were counted, respectively, for the control: T1 (5g fragment), T2 (10g fragment), T3 (15g fragment) and T0 (20g fragment). In the event of a shortage of planting material, the bulb can be cut into mini-pieces of around 10g, i.e., 2/4 of a bulb, in order to increase the rejection potential and thus produce planting material.